Effect of window orientation on the thermal performance of electrochromic glass - Jianan Wen; Jian Sun; Xi Meng (Case Studies in Thermal Engineering)
The utilization of electrochromic glass enables the dynamic adjustment of solar radiation absorption, achieved through the alteration of glass transmittance. This results in enhanced seasonal adaptability of the building and an elevated level of energy efficiency. This study examines the impact of electrochromic glazing on the thermal environment of building interiors, with a particular focus on the influence of composite electrochromic glazing window orientation on this environment. Therefore, two cell models are constructed with normal glass and electrochromic glass, respectively. Transient temperatures of indoor air and two glass surfaces were monitored to reveal the thermal and optical performance of electrochromic glass with considering three window orientations of eastward, southward and westward. The experimental results demonstrate that, in comparison with traditional double-layer glazing, double-layer glazing with electrochromic glass has the potential to significantly reduce the indoor air temperature of the cell model, particularly in the tinted state. The installation of double-layer electrochromic glazing in east, south and west-facing windows under the tinted state has been observed to reduce the average daytime temperatures by 10.44 °C, 9.57 °C and 10.59 °C, respectively, and the maximum daytime temperatures by 24.3 °C, 12.31 °C and 27.16 °C. It can be observed that the orientation of windows has a considerable impact on the cooling benefits of double-layer electrochromic glazing, with the most notable effects observed in west-facing windows, followed by east and south-facing windows. Additionally, there were significant temporal effects. Correlation analysis with meteorological parameters demonstrated that window orientation plays a pivotal role in determining the intensity of solar radiation received by vertical window.